Hassallia littoralis sp. nov. (Cyanobacteria, Microchaetaceae) from Mexico’s marine supralittoral based on morphological and molecular evidence - González-Resendiz, Laura; León-Tejera, Hilda Patricia; Díaz-Larrea, Jhoana; Alba-Lois, Luisa; Segal-Kischinevzky, Caludia (Phytotaxa, 2013)
A new species of Hassallia (Cyanobacteria, Nostocales, Microchaetaceae) from a supralittoral tropical marine biotope is described. Hassallia littoralis is a false-branched nostocalean cyanobacterium with caespitose free filaments or with fasciculated individual filaments not in a common sheath. Filaments are mainly heteropolar, bearing mono- and bi-pored heterocysts and isopolar or heteropolar hormogonia. The sheath is often widening, with pronounced rounded terminals. This new species is defined according to molecular, morphological and ecological criteria, considering data from different stages of its life cycle as well as the 16S rRNA partial gene sequence.